2010
DOI: 10.5551/jat.2964
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level of Platelet-Derived Microparticles Is Associated with Coronary Heart Disease Risk Score in Healthy Men

Abstract: Aim:The aim of this study was to clarify the relationship between platelet-derived microparticles (PDMPs) and the Framingham 10-yr coronary heart disease (CHD) risk score. Methods: A cross-sectional study of healthy volunteers free of medication, and cardiovascular or cerebrovascular disease was conducted. The subjects were 190 Japanese men (median age 41). An ELISA kit and monoclonal antibodies against CD42b and CD42a (glycoprotein Ib and IX) were used. Results: PDMPs are correlated with platelet count, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 48 publications
0
43
0
1
Order By: Relevance
“…However, it is assumed that the PDMP level changes with the platelet count because PDMPs are released by platelets. Many previous reports have shown that there is a positive correlation between the platelet count and PDMP level as measured by ELISA and FCM in healthy individuals 38,39) . Moreover, Joop and coworkers used FCM and suggested that the PDMP level is simply a reflection of the platelet count 16) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…However, it is assumed that the PDMP level changes with the platelet count because PDMPs are released by platelets. Many previous reports have shown that there is a positive correlation between the platelet count and PDMP level as measured by ELISA and FCM in healthy individuals 38,39) . Moreover, Joop and coworkers used FCM and suggested that the PDMP level is simply a reflection of the platelet count 16) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…137 The association between the Framingham risk score and the numbers of PMPs, LMPs, EPCMPs, and EMPs was evaluated. 126,142,143 From these studies, only 1 was prospective, including 488 patients with various CVD risk factors who were observed for a mean of 36 months. 142 These reports are promising.…”
Section: Leukocyte-derived Microparticles and Cardiovascular Diseasesmentioning
confidence: 99%
“…5 They derive from various cells, most notably platelets, but also leucocytes, lymphocytes, erythrocytes, and endothelial cells. MP are present in a small amount in the circulation of healthy patients, 6 but their levels increase in patients with hypercoagulative states, including disseminated intravascular coagulation, 7 ACS, 8,9 peripheral artery disease (PAD), 10 diabetes mellitus, 11 and systemic inflammatory diseases. 12 Endothelial MP (EMP), in particular, are thought to be markers of endothelial injury and are released under stimulation by endothelium activating agents, such as complement fragments 13 or tumor necrosis factor alfa, 14 while platelet MP (PMP) are considered markers of platelet activation.…”
mentioning
confidence: 99%